Análise da capacidade de infiltração em pavimento permeável de blocos de concreto intertravado instalados no campus da UTFPR-CM - Mantovani, Luiz Henrique Vidal (2025)
This study aims to analyze the infiltration rate of interlocking concrete block pavements installed at the Federal University of Technology – Paraná, Campo Mourão Campus. Urban drainage plays a key role in mitigating problems such as floods and inundations, which are exacerbated by soil impermeabilization due to unregulated urban growth, especially in large urban areas where impermeable surfaces are extensive. In this context, Sustainable Urban Drainage Systems (SUDS) are considered effective solutions for stormwater management, promoting greater soil infiltration and reducing surface runoff. The study conducted permeability tests on interlocking concrete blocks, resulting in average values of 1.39×10⁻⁵ ±0.08×10⁻⁵ m/s (50.14 ±2.92 mm/h), 1.34×10⁻⁵ ±0.05×10⁻⁵ m/s (48.08 ±1.97 mm/h), and 2.02×10⁻⁵ ±0.09×10⁻⁵ m/s (72.71 ±3.24 mm/h). These values align with the ranges observed in the literature, such as the coefficients reported by Gris et al. (2020), with 5.89×10⁻⁵ m/s (212.21 mm/h), and by Martins (2014), ranging from 1.24×10⁻⁵ m/s (44.92 mm/h) to 8.79×10⁻⁶ m/s (31.66 mm/h). Conversely, the results found by Santos et al. (2015), between 1.76×10⁻⁶ m/s (6.36 mm/h) and 2.18×10⁻⁶ m/s (7.87 mm/h), and by Zunta (2021), between 3.19×10⁻⁵ m/s (114.66 mm/h) and 1.92×10⁻⁴ m/s (690.63 mm/h), indicate greater variability in permeability. The values obtained in this study demonstrate that the analyzed blocks exhibit performance consistent with other reported tests, reinforcing their efficiency in managing stormwater and reducing surface runoff. Permeable pavements, specifically interlocking concrete blocks, are presented as sustainable alternatives that contribute to effective stormwater management and sustainable urban development.